2018
DOI: 10.1007/s10236-018-1131-2
|View full text |Cite
|
Sign up to set email alerts
|

Variability of nutrients and carbon dioxide in the Antarctic Intermediate Water between 1990 and 2014

Abstract: Antarctic Intermediate Water (AAIW) formation constitutes an important mechanism for the export of macronutrients out of the Southern Ocean that fuels primary production in low latitudes. We used quality-controlled gridded data from five hydrographic cruises between 1990 and 2014 to examine decadal variability in nutrients and dissolved inorganic carbon (DIC) in the AAIW (neutral density range 27 < γ n < 27.4) along the Prime Meridian. Significant positive trends were found in DIC (0.70 ± 0.4 μmol kg −1 year −… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 66 publications
1
19
0
7
Order By: Relevance
“…In addition to an oxygen decrease in tropical regions, Schmidtko et al (2017) showed a decrease of oxygen levels by 2-5 mmol.m -3 in the regions of formations of AAIW. Based on repeated cruise observations, Panassa et al (2018) highlighted an increase of the apparent oxygen utilization in the core of the AAIW, related to a 5 % increase in nutrient concentrations from 1990 to 2014. The transport of this modified AAIW, poorer in oxygen and richer in nutrients, toward the low latitudes both by small scale processes (section 3) and at the equator by the EICS (section 4), may explain a significant part of the occuring deoxygenation in the equatorial ocean.…”
Section: Implication For Biogeochemical Cyclesmentioning
confidence: 99%
“…In addition to an oxygen decrease in tropical regions, Schmidtko et al (2017) showed a decrease of oxygen levels by 2-5 mmol.m -3 in the regions of formations of AAIW. Based on repeated cruise observations, Panassa et al (2018) highlighted an increase of the apparent oxygen utilization in the core of the AAIW, related to a 5 % increase in nutrient concentrations from 1990 to 2014. The transport of this modified AAIW, poorer in oxygen and richer in nutrients, toward the low latitudes both by small scale processes (section 3) and at the equator by the EICS (section 4), may explain a significant part of the occuring deoxygenation in the equatorial ocean.…”
Section: Implication For Biogeochemical Cyclesmentioning
confidence: 99%
“…Recently, large interannual variability in high-latitude Southern Hemisphere surface climate (Jones, Gille, et al, 2016) and a large decadal variability of the SO carbon sink (Landschützer et al, 2015;Le Quéré et al, 2007) have been reported. Furthermore, nutrient concentrations show signals of variability or change in multiple regional studies from surface to depth (Ayers & Strutton, 2013;Hoppema et al, 2015;Iida et al, 2013;Panassa et al, 2018;Pardo et al, 2017). Given that mode and intermediate water masses reach the subtropical thermocline on a time scale of a few decades (Jones, Meijers, et al, 2016;Rodgers et al, 2003), it is very likely that these changes may reappear in the low latitudes on a time scale relevant to human anthropogenic CO 2 emissions and emission reduction endeavors (Palter et al, 2010;Pasquier & Holzer, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Esse mecanismo alimenta de 33% a 75% da produtividade primária tropical entre 30 o N a 30 o S (Palter et al 2010) com uma escala espacial de menos de 40 anos para todo o nutriente ser utilizado neste espaço. Palter et al (2010) ainda afirmam que os nutrientes da SAMW alimentam primeiro a produtividade primária ao sul de 20 o S. Este mecanismo conseguiu explicar o resultado em diversos estudos variando de tópicos desde a biogeoquímica do Atlântico norte a estudos paleoclimáticos (Marinov et al 2006;Moore et al 2009;Anderson et al 2009) e levando a formulação de outros estudos pelo desdobramento desse mecanismo (Ayers and Strutton 2013;Panassa et al 2018;Palter et al 2011).…”
Section: Relação Da Moc Na Clorofilaunclassified
“…O primeiro é a Oscilação Antártica (AAO). Sua escolha foi baseada pelo seu efeito nos ventos de oeste na região subpolar, que por sua vez alteram a ressurgência antártica, afetando assim diretamente a concentração nutrientes que adentram na Água Modal Subantártica (SAMW) e AIA (Água Intermediária Antártica) e que serão transportados pela MOC do Atlântico Sul (Thompson et al 2011;Marshall 2003;Panassa et al 2018). Além disso, a AAO pode afetar o vazamento das Agulhas, que traz águas do Oceano Índico no Atlântico Sul (Biastoch and Böning 2013;Beal et al 2011;Marini, Frankignoul, and Mignot 2011).…”
Section: íNdices Climáticosunclassified
See 1 more Smart Citation